2021
DOI: 10.1001/jamadermatol.2021.3459
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus (Rapamycin) for Slow-Flow Malformations in Children

Abstract: IMPORTANCESirolimus is increasingly being used to treat various vascular anomalies, although evidence of its efficacy is lacking.OBJECTIVE To assess the efficacy and safety of sirolimus for children with slow-flow vascular malformations to better delineate the indications for treatment. DESIGN, SETTING AND PARTICIPANTSThis multicenter, open-label, observational-phase randomized clinical trial included 59 children aged 6 to 18 years with a slow-flow vascular malformation who were recruited between September 28,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 48 publications
4
43
0
1
Order By: Relevance
“…Clinical response to sirolimus, including symptomatology and QOL, in CLVM patients has previously been reported in small case reports and case series with similar results 18,19 . Additionally, the PERFORMUS Trial, as a secondary outcome, reported improvements in pain and bleeding in patients with CLVM treated with sirolimus 20 …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Clinical response to sirolimus, including symptomatology and QOL, in CLVM patients has previously been reported in small case reports and case series with similar results 18,19 . Additionally, the PERFORMUS Trial, as a secondary outcome, reported improvements in pain and bleeding in patients with CLVM treated with sirolimus 20 …”
Section: Discussionsupporting
confidence: 62%
“…18,19 Additionally, the PERFORMUS Trial, as a secondary outcome, reported improvements in pain and bleeding in patients with CLVM treated with sirolimus. 20 Some patients with CLVM have overgrowth of bone and/or soft tissue due to the gain-of-function PIK3CA mutation in those affected tissues. While sirolimus is known to decrease cystic components of LM, its ability to adequately control tissue overgrowth in PROS remains questionable and was not specifically evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sirolimus (or rapamycin) inhibits lymphangiogenesis by interfering with the PI3K/AKT/mTOR signaling pathway. It has been used in complicated LMs for 10 years [31][32][33][34][35][36][37][38][39]. Many studies have confirmed its effectiveness, albeit partial (up to 90%), delayed (after 2 weeks to 6 months of treatment) and suspensive.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Regular clinical and biological monitoring (approximately 1 month after treatment initiation, then every 2-3 months) is required. Sirolimus trough concentration should be measured for dose adjustment (target concentration approximately 3-12 ng/ml) Drug interactions should be routinely checked [34][35][36][37][38][39].…”
Section: Medical Treatmentmentioning
confidence: 99%
“…It is also incumbent upon us to consider the adjunctive use of medical therapies such as the mTOR inhibitor Sirolimus and more recently Alpelisib, targeting the PIK3CA mutation, a somatic mutation associated with overgrowth and lymphatic malformations. These targeted therapies may work synergistically with sclerotherapy to affect a greater response especially in mixed lesions and those that have airway compromise [7].…”
Section: Introductionmentioning
confidence: 99%